2020
DOI: 10.3390/microorganisms8101490
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gp120 Inner Domain (ID2) Immunogen Doses on Elicitation of Anti-HIV-1 Functional Fc-Effector Response to C1/C2 (Cluster A) Epitopes in Mice

Abstract: Fc-mediated effector functions of antibodies, including antibody-dependent cytotoxicity (ADCC), have been shown to contribute to vaccine-induced protection from HIV-1 infection, especially those directed against non-neutralizing, CD4 inducible (CD4i) epitopes within the gp120 constant 1 and 2 regions (C1/C2 or Cluster A epitopes). However, recent passive immunization studies have not been able to definitively confirm roles for these antibodies in HIV-1 prevention mostly due to the complications of cross-specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…We recently developed an immunogen referred to as inner domain 2 (ID2), which stably expresses the conformational Cluster A epitope target within a minimal structural unit of gp120 [ 26 ]. Immunization studies in BALB/c mice with ID2 demonstrated that ID2 was highly immunogenic and that the Cluster A-specific responses were induced at levels that provided potent Fc-effector activities, including ADCC [ 27 , 28 , 29 , 30 ]. Here, we describe the engineering, functional analyses and immunogenicity of ID2-V1V2, an immunogen variant that incorporates both the Cluster A and V1V2 regions of HIV-1 Env to induce Fc-effector function responses to both epitope targets implicated in the protective effect of the RV144 vaccine trial.…”
Section: Introductionmentioning
confidence: 99%
“…We recently developed an immunogen referred to as inner domain 2 (ID2), which stably expresses the conformational Cluster A epitope target within a minimal structural unit of gp120 [ 26 ]. Immunization studies in BALB/c mice with ID2 demonstrated that ID2 was highly immunogenic and that the Cluster A-specific responses were induced at levels that provided potent Fc-effector activities, including ADCC [ 27 , 28 , 29 , 30 ]. Here, we describe the engineering, functional analyses and immunogenicity of ID2-V1V2, an immunogen variant that incorporates both the Cluster A and V1V2 regions of HIV-1 Env to induce Fc-effector function responses to both epitope targets implicated in the protective effect of the RV144 vaccine trial.…”
Section: Introductionmentioning
confidence: 99%